Method for Testing Virus Stocks for Viral Contaminants - Hampil, Bettylee (1969)
A practical method for testing the purity of virus stocks has been developed and applied to reference stocks of enteroviruses. The method requires the use of a reference antiserum that is substantially free from heterotypic antibody. When selected dilutions of this antiserum are reacted with high concentrations of virus, virus intentionally allowed to escape neutralization is recovered and then identified. A contaminating virus present as a minor component of the population has a far greater probability of being revealed under the conditions of this “breakthrough” test than under the commonly used virus identity tests which customarily employ approximately 100 TCD(50) of virus and, therefore, only identify the major component of the virus population. The breakthrough test described has been used for tests of 104 reference stocks of all the enteroviruses that propagate in monkey kidney cells and human amnion cells. Although all the materials had been previously tested and approved by the commonly employed virus identity test, the breakthrough test in two instances revealed contaminating heterotypic enteroviruses present at a very low titer in the stocks. Without resorting to the stringent, elaborate, and expensive tests for absolute purity, such as those that are required to assure safety of vaccines, the use of the breakthrough test described provides reasonable assurance of purity for stock viruses to be employed as diagnostic reagents or for general laboratory research purposes where a multiplicity of viral agents and antisera are required.